Keep Your Fingers Crossed! - Damisch, Lysann; Stoberock, Barbara; Mussweiler, Thomas (Psychological Science, 2010)
Superstitions are typically seen as inconsequential creations of irrational minds. Nevertheless, many people rely on superstitious thoughts and practices in their daily routines in order to gain good luck. To date, little is known about the consequences and potential benefits of such superstitions. The present research closes this gap by demonstrating performance benefits of superstitions and identifying their underlying psychological mechanisms. Specifically, Experiments 1 through 4 show that activating good-luck-related superstitions via a common saying or action (e.g., “break a leg,” keeping one’s fingers crossed) or a lucky charm improves subsequent performance in golfing, motor dexterity, memory, and anagram games. Furthermore, Experiments 3 and 4 demonstrate that these performance benefits are produced by changes in perceived self-efficacy. Activating a superstition boosts participants’ confidence in mastering upcoming tasks, which in turn improves performance. Finally, Experiment 4 shows that increased task persistence constitutes one means by which self-efficacy, enhanced by superstition, improves performance.